Using Influence Matrices as a Design and Analysis Tool for Adaptive Truss and Beam Structures - Steffen, Simon; Weidner, Stefanie; Blandini, Lucio; Sobek, Werner (Frontiers in Built Environment, 2020)
Due to the already high and still increasing resource consumption of the building industry, the imminent scarcity of certain building materials and the occurring climate change, new resource- and emission-efficient building technologies need to be developed. Especially since these effects are further amplified by the growth of population. One proposed technology is that of adaptive load bearing structures. Integrating sensors, actuators and a control unit into the structure enables the structure to react to external loads, when needed. For example, when high but rare loads occur. The goal of the adaptation could be the reduction of deflections or the homogenization of stresses. This allows for ultra-lightweight structures with reduced material consumption and emissions. The two main questions of adaptive truss and beam structures are, first, the question of optimal actuator placement and second, which type of typology (truss, frame, etc.) is most effective for adaptive load bearing structures. One approach for finding the optimal configuration is that of so called influence matrices. Influence matrices, as introduced in this paper, are a type of sensitivity matrix, which describe how and to which extend various properties of a given load bearing structure can be influenced by different types of actuation principles. The method of influence matrices is exemplified by a series of studies on different configurations of a truss structure.